Rare bird documentation form for Peregrine Falcon at Grammer Grove in 1986 - Proescholdt, Bethet al (1986)
Rare bird documentation form for a Peregrine Falcon at Grammer Grove in Marshall County, IA on September 20, 1986. Epson - sheet feed